2016
DOI: 10.1016/j.jval.2016.03.1445
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidities and Symptoms among Endometriosis Patients: A Systematic Literature Review

Abstract: Objectives: Endometriosis patients could experience a myriad of comorbidities. This study aimed to systematically review comorbidities and symptoms reported by endometriosis patients in the medical literature. MethOds: MEDLINE and EMBASE databases were searched for articles reporting comorbidities and/or symptoms among endometriosis patients published in English between 2000 and 2013. The following search terms were used in the search process: "endometriosis, or endometrioses, or endometrioma$

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The varying degrees of involvement by endometriosis resulted in symptoms of varying severity. Buchanan, 2017;Soliman et al, 2016). However, the results indicated that, in addition to causing physical symptoms, endometriosis had a significant impact on the emotional well-being of the participants, which slightly differed from the findings of other studies.…”
Section: The Associations Between Symptom Distress and H-qolmentioning
confidence: 79%
See 1 more Smart Citation
“…The varying degrees of involvement by endometriosis resulted in symptoms of varying severity. Buchanan, 2017;Soliman et al, 2016). However, the results indicated that, in addition to causing physical symptoms, endometriosis had a significant impact on the emotional well-being of the participants, which slightly differed from the findings of other studies.…”
Section: The Associations Between Symptom Distress and H-qolmentioning
confidence: 79%
“…The varying degrees of involvement by endometriosis resulted in symptoms of varying severity. Common symptoms include abnormal uterine bleeding, menorrhagia, pelvic pain, abnormal intestinal function, frequent or urgent urination, lower back pain, and dyspareunia (De La Cruz & Buchanan, 2017; Soliman et al, 2016). However, the results indicated that, in addition to causing physical symptoms, endometriosis had a significant impact on the emotional well‐being of the participants, which slightly differed from the findings of other studies.…”
Section: Discussionmentioning
confidence: 99%
“…A set of 22 comorbid chronic conditions that frequently co-occur with endometriosis was selected from a published literature review and reviewed by a clinical expert (Dr. Craig A. Winkel, MD) [ 17 ]. The set includes comorbidities related to gynecological, mental health, gastrointestinal, cancer, and autoimmune conditions (Online Supplementary Material, Table S.1).…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have revealed a higher prevalence of allergies and autoimmune diseases in patients with endometriosis 10 – 12 . However, the relationship between endometriosis and SLE has not been studied thoroughly and remains unclear.…”
Section: Introductionmentioning
confidence: 99%